Evolution mechanism of diesel ignition with injection pressure under different spray wet-wall conditions at low temperatures. (15th December 2022) - Wu, Han; Dong, Xinyi; Shi, Zhicheng; Li, Haiying; Miao, Sheng; Cao, Weiren; Bo, Yaqing; Zhang, Lu; Li, Xiangrong
Graphical abstract: Highlights: The mixture suitable for a hot flame decreases with increasing injection pressure. High injection pressures under liquid-phase spray impingement easily cause misfires. Ignition delay shortens and then extends with injection pressure for vapor wet-wall. The difference in ignition evolution depends on transition from cool to hot flame. Increased injection pressure causes heat release to decrease due to fuel diffusion. Abstract: The effect of injection pressure on diesel ignition has been widely studied, but the conclusions are different or even contradictory. Thus, the 3-D simulation was conducted at injection pressures of 40–280 MPa under different spray wet-wall conditions. The results show that as the injection pressure increases, the fuel injection ends earlier, so the mass fraction of the mixture suitable for ignition (0.8 <  φ  < 1.6) reaches its maximum earlier and starts to decrease. Its value is sharply reduced shortly after the cool flame reaction, especially for the liquid-phase spray impingement. Accordingly, the ignition delay under liquid impingement increases with the injection pressure, and misfire occurs at 160 MPa due to the too low mixture concentration ( φ  = 0.6) in the hot flame stage. In the case of vapor impingement, as the injection pressure increases from 40 MPa to 280 MPa, the ignition delay shortens and then extends, and the transition occurs at 220 MPa. Ignition delay in free spray decreases with increasing injection pressure. The above variation depends mainly on the transition from a cool flame to a hot flame. In addition, with the increase of injection pressure, more than 90 % of the fuel film remains even after intense combustion. Although the instantaneous heat release rate increases, the total heat release decreases significantly, which is caused by the mixture concentration being too lean due to excessive fuel diffusion and thus incomplete combustion. In conclusion, low-pressure injection is preferred for liquid impingement, while moderately elevated injection pressures under vapor impingement and free spray facilitate fast ignition and optimized heat release.